2016
DOI: 10.1108/jmp-07-2015-0259
|View full text |Cite
|
Sign up to set email alerts
|

Heavy work investment, personality and organizational climate

Abstract: Purpose – The purpose of this paper is to assess the relative importance of personality and organizational climate for two forms of heavy work investment; workaholism, a “bad” and work engagement, which represents a “good” kind of heavy work investment. More specifically, it is hypothesized that workaholism is positively related to neuroticism (H1) and that work engagement is negatively related to neuroticism and positively to the remaining Big Five personality traits (H2). In addition it is hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
119
1
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(157 citation statements)
references
References 53 publications
10
119
1
27
Order By: Relevance
“…Nesse sentido, pode-se pensar que o PA, por não ter uma delimitação das horas a serem trabalhadas, também tem elevada a quantidade de tarefas laborais assumidas, já que estas constituem sua renda salarial. As horas de trabalho do PA se complementam no espaço reservado à vida pessoal, gerando uma carga horária mais elevada para a realização de atividades que resultam em maior TE (Schaufeli, 2016). O excesso de trabalho para além de uma jornada de horas de trabalho equilibrada entre vida pessoal e profissional implica no aumento de TE (Mazzetti et al, 2014), principalmente em PA, no qual os limites entre trabalho e vida pessoal podem ser transgredidos facilmente (Andreassen et al, 2016).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nesse sentido, pode-se pensar que o PA, por não ter uma delimitação das horas a serem trabalhadas, também tem elevada a quantidade de tarefas laborais assumidas, já que estas constituem sua renda salarial. As horas de trabalho do PA se complementam no espaço reservado à vida pessoal, gerando uma carga horária mais elevada para a realização de atividades que resultam em maior TE (Schaufeli, 2016). O excesso de trabalho para além de uma jornada de horas de trabalho equilibrada entre vida pessoal e profissional implica no aumento de TE (Mazzetti et al, 2014), principalmente em PA, no qual os limites entre trabalho e vida pessoal podem ser transgredidos facilmente (Andreassen et al, 2016).…”
Section: Resultsunclassified
“…A AT tem sido explicada por variáveis individuais -sociodemográficas, motivação/foco regulatório, características de personalidade (Clark, 2017;Mazzetti, Schaufeli, & Guglielmi, 2014;Schaufeli, 2016;Tabassum & Rahman, 2012), satisfação com a vida (Pinheiro & Carlotto, 2016) -e laborais, como o tipo de profissão (Taris et al, 2012), trabalhar individualmente ou em equipe (Littman-Ovadia, Balducci, & Ben-Moshe, 2014), remuneração (Sharma & Sharma, 2011), tempo de atuação profissional (Mazzetti et al, 2014;Taris et al, 2012), carga horária semanal (Carlotto, 2011;Castillo & Gómez, 2012;Mazzetti et al, 2014) e quantidade de horas utilizadas com tecnologia da informação e comunicação (Andreassen, 2014). No que diz respeito às sociodemográficas, estudos revelam índices mais elevados em mulheres (Littman-Ovadia, Balducci, & Ben-Moshe, 2014), profissionais mais jovens (Mazzetti, Schaufeli, & Guglielmi, 2014;Taris et al, 2012), de maior escolaridade (Andreassen et al, 2014) e menor salário (Sharma & Sharma, 2011).…”
unclassified
“…Moreover, Clark, Lelchook, and Taylor () conducted a study on working students and found that extraversion, neuroticism, and openness to experience were related to workaholism. Due to the incongruent results, Schaufeli () proposed that the disparate findings are mostly attributable to the measures used to assess workaholism and the equivocal definitions of this variable. Furthermore, Schaufeli () suggested that when the measures utilized to assess workaholism reflect its fundamental elements (i.e., compulsive and excessive working), then workaholism will strongly correlate with neuroticism.…”
Section: Workaholism Antecedentsmentioning
confidence: 99%
“…Due to the incongruent results, Schaufeli () proposed that the disparate findings are mostly attributable to the measures used to assess workaholism and the equivocal definitions of this variable. Furthermore, Schaufeli () suggested that when the measures utilized to assess workaholism reflect its fundamental elements (i.e., compulsive and excessive working), then workaholism will strongly correlate with neuroticism. Although results confirmed this proposition in a sample of 1,973 Dutch participants, Schaufeli () also found that extraversion and agreeableness were significantly related to workaholism.…”
Section: Workaholism Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation